ENHANCEMENT OF HEAT TRANSFER USING CONICAL RING INSERTS IN TUBE - Ms. Nishidha A. Lokhande, Dr. M. Basavaraj (International Journal of Research Science and Management, 2016)
The development of high performance heat exchangers have gained importance in various engineering application such as in air conditioning, thermal power plant, automotives, space vehicle, heat sink, for electronics and so on. To reduce the cost and size of heat exchanger which may lead to considerable saving in material cost. Passive heat transfer augmentation tools and method can play an important role in design of heat exchanger are twisted tape, wire coil, ribs, baffles, conical ring and helical coil etc. A detailed study analysis of conical ring passive heat transfer augmentation technique is made.